The Efficiency of Applying Compressed Sampling and Multi-Resolution Into Ultrasound Tomography - Quang Huy, Tran; Dung Nguyen, Van; Tran, Duc Tan (Ingeniería Solidaria, 2019)
Introduction: This publication is the product of  research developed within the research lines of the Smart Sensing, Signal Processing, and Applications (3SPA)  research  group  throughout  2018,  which  supports  the  work  of  a  doctor’s degree at VNU University of Engineering & Technology, Vietnam.Problem: The limitations of diagnostic ultrasound techniques using echo information has motivated the study of new imaging models in order to create additional quantitative ultrasound information in multi-model imaging devices. A promising solution is to use image sound contrast because it is capable of detecting changes in diseased tissue structures. Ultrasound tomography shows speed-of-sound changes in the propagation medium of sound waves. This technique is primarily used for imaging cancer-causing cells in womens’ breasts. The Distorted Born Iterative Method (DBIM), based on the first-order Born approximation, is an efficient diffraction tomography approach. The compressed sensing technique is utilized for DBIM to obtain the high-quality ultrasound image, although the image reconstruction process is quite long.Objective: The objective of the research is to propose an combined method for the efficient ultrasound tomography.Methodology: In this paper, we proposed an approach to enhance the imaging quality and to reduce the imaging time by applying the compressed sensing technique along with the multi-resolution technique for the DBIM.Results: The simulation results indicate that the imaging time is reduced by 33% and the imaging quality is improved by 83%.Conclusion: This project seeks to propose an improvement in ultrasound tomography. The simulated results confirmed the realibility of the propsed method.Originality: Through this research, a combined method of compressed sensing and multiple resolution are formulated for the first time in ultrasound tomography.Limitations: The lack of experiments to confirm the proposed method.
Keywords: Ultrasound; Tomography; Echo Information; Speed-of-Sound; Inverse Scattering; Distorted Born Iterative Method (DBIM); Compressed Sensing (CS); Multi-Resolution (MR)